Neoadjuvant treatment for borderline resectable pancreatic adenocarcinoma is associated with higher R0 rate compared to upfront surgery. (2nd September 2021) - Terlizzi, Mario; Buscail, Etienne; Boussari, Olayidé; Adgié, Sarah; Leduc, Nicolas; Terrebonne, Eric; Smith, Denis; Blanc, Jean-Frédéric; Lapuyade, Bruno; Laurent, Christophe; Chiche, Laurence; Belleannée, Geneviève; et al.
Abstract: Background: Neoadjuvant treatment (NAT) is debated for borderline resectable pancreatic cancer (BRPC). This retrospective study assessed the impact of NAT on R0 rate and survival for BRPC patients in comparison with upfront surgery (US). Material and methods: Between 2010 and 2017 patient records for all consecutive patients treated for BRPC according to NCCN 2017 were reviewed. The endpoints analysed were R0 rate, recurrence-free-survival (RFS) and overall survival (OS). Results: Seventy-nine patients were included: 63 (79.7%) patients received NAT and 16 (20.3%) were upfront operated. NAT consisted in FOLFIRINOX (median cycles: 5, range 4–8) followed by chemoradiation ( n = 55, 87.3%, median dose: 54 Gy). Thirty-nine (61.9%) patients had resection. R0 rate was higher in the NAT group considering a margin clearance of 0 mm (94.9%) or 1 mm (89.7%) compared to the US group (68.8% and 43.8% respectively). In the whole population, median RFS was 12.6 [95%CI: 10.5–22.1] in the NAT group vs 7.7 [95%CI: 4.4–14] months in the US group ( p < 0.01). Median OS was 29.0 [95%CI: 23.5–63.1] and 27.2 [95%CI: 11.6–38.8] months in the NAT and US groups respectively ( p = 0.06). In operated patients the NAT group achieved better RFS and OS than the US group ( p < 0.01 for both). In multivariate analysis NAT, surgical resection and age <65 ( p < 0.01 for both) were prognostic of RFS. NAT, surgical resection and adjuvant chemotherapy were prognostic of OS ( p < 0.05 for all). In operated patients ( n = 55) multivariate analysis showed that N1 status was associated with decreased RFS; age < 65 and NAT were associated with a longer RFS. Receiving a NAT, an adjuvant chemotherapy and achieving a ypT0-1N0 status were associated with better OS. NAT was well tolerated with 14.3% grade ≥ 3 toxicities. Conclusion: NAT permitted a high R0 rate with a 0- or 1-mm clearance margin and was associated with better RFS and OS for patients with BRPC.